WHEEL-MADE TERRACOTTA AND HOLLOW BULL FIGURINES FROM THE KNIDOS TERRITORY - Derviş Ozan TOZLUCA (Journal of Ancient History and Archaeology)
Terracotta Bull Figurines are among the most significant finds from the 8th and 7th centuries BCE in the Knidos territory. Major centers where these figurines have been discovered include the Emecik Apollo Sanctuary, Knidos, Burgaz, and Kumyer. In the Knidos territory, bull figurines were produced using three different techniques: hand-shaped, wheel-made, and hollow-formed. Figurines found at Emecik, Knidos, and Kumyer were crafted in three distinct body types. The bull figurines, which have survived to this day in fragments, consist of body, head, and leg parts. The bodies of these figurines in this group were made in a cylindrical form on a wheel. The cylindrical bodies were sealed with clay slabs on both ends, and details such as the head, legs, penis, anus, and tail were added later. The outer surface of the wheel-made bodies was burnished with a spatula-like tool, thus removing the wheel marks. In the hollow-formed figurines, the body was shaped by hand. It is likely that hollow bull figurines required less time and skill compared to the wheel-made ones. In our study, wheel-made and hollow bull figurines, which had not been comprehensively evaluated before, have been assessed, identified, dated, and their significance for the Dodecanese region explained.